Perang Salib Dan Dampaknya Pada Dunia - Yuslia Styawati; Mubaidi Sulaeman (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
This article discusses the other side of the Crusades. The Crusades that occurred thousands of years ago, apart from having the impact of geopolitical changes at that time, turned out to have a significant impact on social, cultural, scientific and economic changes on European Muslims and Christians at that time. The Crusades are the longest and biggest war in the history of world civilization. Efforts to save the territory under the friction of religious doctrine between Islam and Christianity caused huge losses to both of them, both morally and materially. Although there are some advantages from the contact of two different civilizations, the two of them still cannot be avoided. The Crusade is the longest and biggest war in the history of world civilization. Efforts to save the territory under the friction of religious doctrine between Islam and Christianity caused great losses to both of them, both morally and materially. Although there are still some advantages from the contact between two different civilizations, the two of them have still been unable to avoid the enormous losses to date.